PREDICTION OF PASSENGER PRODUCTIVITY AT THE KUALA TUNGKAL RO-RO FERRY PORT ON THE KUALA TUNGKAL – TELAGA PUNGGUR LINE - Yulia Puspita Sari; Ulya, Febriyanti Himmatul; Agustina, Elfita; Zakki, Farhan (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2025)
Passenger productivity at the port plays a crucial role in supporting the sustainability of port operations. Predicting the number of passengers at the port can be used as a reference for preparing port service readiness. The Kuala Tungkal Ferry Port, on the Kuala Tungkal – Telaga Punggur route, connects Jambi Province with the Riau Islands Province. The purpose of this study is to predict the number of passengers on Eid transportation in 2026. The historical data used is data from 14 days before Eid al-Fitr until 7 days of Eid al-Fitr from 2020 to 2025. The analysis method used is the FORECAS.ETS method, the application of which is carried out in Excel. After conducting the analysis, the prediction was that the highest number of passengers would be seven days after Eid al-Fitr, with 882 people. This prediction was used as a reference for evaluating the port's service readiness. The evaluation, based on Ministerial Decree No. 52 of 2004, determined that the existing waiting area was inadequate to accommodate the number of passengers expected for the 2026 Eid al-Fitr holiday.